Screening and detection of chromosomal copy number alterations in the domestic horse using SNP‐array genotyping data. (19th May 2021) - Pirosanto, Y.; Laseca, N.; Valera, M.; Molina, A.; Moreno‐Millán, M.; Bugno‐Poniewierska, M.; Ross, P.; Azor, P.; Demyda‐Peyrás, S.
Summary: Chromosomal abnormalities are a common cause of infertility in horses. However, they are difficult to detect using automated methods. Here, we propose a simple methodology based on single nucleotide polymorphism (SNP)‐array data that allows us to detect the main chromosomal abnormalities in horses in a single procedure. As proof of concept, we were able to detect chromosomal abnormalities in 33 out of 268 individuals, including monosomies, chimerisms, and male and female sex‐reversions, by analyzing the raw signal intensity produced by an SNP array‐based genotyping platform. We also demonstrated that the procedure is not affected by the SNP density of the array employed or by the inbreeding level of the individuals. Finally, the methodology proposed in this study could be performed in an open bioinformatic environment, thus permitting its integration as a flexible screening tool in diagnostic laboratories and genomic breeding programs.